Analysis of Influence of Compensation and Leadership Style To Employee Performance PT. Feva Indonesia - Purnamasari, Bulawambona Endah; Tridayanti, Rr. Hermien (Quantitative Economics and Management Studies, 2020)
The purpose of this study is to study leadership style and comparison of employee performance. This research was conducted at the company PT. Feva Indonesia. The population used was 60 people. Data collection is done through interviews. The analytical tool used is multiple linear regression techniques. The results of the analysis show a positive leadership style but not significant on employee performance. This shows how leadership style is not related or not significant to employee performance, related to employee performance that requires authoritarian support and cannot be involved in the decision making process. Positive and significant compensation variables on employee performance. This shows that fair and proper assistance is needed to be given to employees, the employee's needs will increase significantly.